A Time‐Based Policy for Empty Container Management by Consignees. Issue 6 (11th February 2019) - Legros, Benjamin; Bouchery, Yann; Fransoo, Jan
Abstract : Despite the many advantages of containerization for goods transportation, the management of empty containers is a major disadvantage, driving costly repositioning operations. We investigate the potential for consignees to manage an inventory of empty containers at their location so as to enable direct reuse of these containers by consignors located in the surroundings. One difficulty is that the detention fees imposed by shipping companies under merchant haulage are nonlinear. Moreover, cleaning and related activities might be necessary if the consignee keeps some empties. These difficulties incentivize consignees to immediately return containers to the sea terminal. Contrary to this practice, we show that managing containers via time‐based threshold policies can save costs. Without cleaning costs, we prove that a time‐based policy with a timeout return time is optimal. We next develop a policy improvement approach to include the cleaning costs in the analysis. This results in a two‐thresholds time‐based policy where the two time thresholds control the admission into and rejection out of the inventory. We next analyze the impact of this proactive management on the level of direct container reuse. This practice enables a high level of direct reuse. It also reduces container repositioning costs. Yet, the incentive to implement our policy varies a lot from one setting to another. In particular, low cleaning costs or high repositioning costs lead to significant costs improvement when implementing our policy. Finally, we further explore if the incentive could be made stronger by modifying the structure and/or purpose of the detention costs.